2019
DOI: 10.1186/s12889-019-6722-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early introduction of complementary feeding and consumption of non-recommended foods among Dutch infants: the BeeBOFT study

Abstract: Background Timing and types of complementary feeding in infancy affect nutritional status and health later in life. The present study aimed to investigate the factors associated with early introduction of complementary feeding (i.e., before age 4 months), and factors associated with infants consumption of non-recommended foods, including sweet beverages and snack foods. Methods This study used cross-sectional data from the BeeBOFT study ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
3
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 51 publications
12
42
3
15
Order By: Relevance
“…Findings of this study are consistent with other studies which have investigated the determinants of dietary behaviors of infants and toddlers and have found that children of younger mothers had less healthy diets than those of older mothers [41,43,[51][52][53][54][55][56]. We did not however, find an independent association with discretionary food intake and maternal education reported in other studies [41,51,[53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings of this study are consistent with other studies which have investigated the determinants of dietary behaviors of infants and toddlers and have found that children of younger mothers had less healthy diets than those of older mothers [41,43,[51][52][53][54][55][56]. We did not however, find an independent association with discretionary food intake and maternal education reported in other studies [41,51,[53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…The early and escalating consumption of energy dense-nutrient poor foods in early childhood is not unique to Australian children. In the Dutch BeeBOFT study 20.2% of infants were consuming sweet beverages daily and 16.5% were consuming snack food daily at 6 months of age [43]. The results of the US 2016 Feeding Infants and Toddler Study (FITS) [44] indicate that 34% of infants aged 6 to 11.9 months had consumed sweets such as cakes, biscuits, muffins, frozen desserts or sugar sweetened beverages, with this proportion rising to 73% of children aged 12 to 17.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO recommends exclusive breastfeeding up to 6 months of age, with continued breastfeeding along with appropriate complementary feeds up to 2 years of age or beyond [6]. The complementary feeding should be initiated in a child, no later than 26 weeks and not before 17 weeks of age [7]. The benefits of exclusive breastfeeding and proper weaning in the growth, development, and prevention of illness in young children are undisputable.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время изучают отсроченные риски употребления при прикорме младенцев продуктов, не предназначенных для них, в т. ч. сладких напитков и снеков [27]. Результаты систематических обзоров показывают, что употребление подслащенных напитков при введении прикорма повышает риск развития ожирения.…”
Section: раннее пищевое программирование и особенности введения блюд unclassified
“…Исследователи подчеркивают связь введения прикорма в возрасте до 4 мес с последующим развитием ожирения у детей, находящихся на искусственном вскармливании, но при этом отмечают необходимость дифференцированной оценки продуктов прикорма [34]. В частности, указывают на возможную негативную роль содержащихся в промышленных прикормах насыщенных жиров, избытка сахаров и натрия [35]; причем доля младенцев, получающих эти продукты в возрасте до 4 мес в некоторых регионах, превышает 20% [27]. Метаанализ результатов 81 исследова-ния показал, что у здоровых доношенных детей риск формирования избыточной массы тела или преобладания жировой массы в составе тела не различался в когортах, получивших прикорм в возрасте 4-5 или в 6 мес жизни, хотя в отдельных работах связь введения прикорма в возрасте до 4 мес с более высокой частотой ожирения была подтверждена [28].…”
Section: сроки введения прикорма и их связь с риском отсроченной патоunclassified